Attaining fairness in construction cost consultancy pricing services: A case study in Ghana. Issue 4 (3rd October 2016) - Owusu-Manu, De-Graft; John Edwards, David; Adesi, Michael; Badu, Edward; Love, Peter E.D.
Abstract : Purpose: Price fairness is important amongst construction and engineering consultants because a perceived lack of it engenders unwillingness to pay amongst clients. This can create contractual disputes that negatively impact upon a consultant's ability to generate sufficient revenue to ensure business continuity and survival. With this in mind, this research aims to analyse the pricing measurement forces needed to attain pricing fairness within a Ghanaian construction cost consultancy practice. Specific objectives are to identify the key variables responsible for price fairness within cost consultant services and to establish any interrelationships between them. Design/methodology/approach: This study leans towards the positivist methodological tradition by adopting a quantitative approach. A survey questionnaire was distributed to a random sample of 79 construction cost consultancies, drawn from a population of 372, who were registered with the Ghana Institution of Surveyors. Hypotheses developed from the literature review were then tested on data collected. Findings: The analysis revealed that fairness of construction cost consultancy services pricing is significantly related to value and affordability, pricing objectives, pricing strategies, taxes and international trade and its effects on inputs for construction cost consultancy services. Originality/value: The paper advances knowledge by providing a basis for the consideration of pricing forces in the valuing of construction cost consultancy services which hitherto has not been the case.